Social Capital and Slum Communities: How to Fulfill Their Basic Needs in Palembang City during The Covid-19 Pandemic - Muhammad Izzudin; Yunindyawati Yunindyawati; Candra Wardana; Putri Wulandari; Muhammad Ibrahim; Tasya Amelia Putri; Januar Eko Aryansah; Sena Putra Prabujaya (Universitas Gadjah Mada, 2023)
The problem of slum settlements is still a major problem faced in Indonesia and other developing countries. One of the triggers for the emergence of slum settlements is due to the high rate of population growth, both through the birth process and the urbanization process. This study discusses the social capital of the people of the slum area of Palembang City in fulfilling basic needs, precisely in the 12 Ulu Village Area, Palembang City during the Covid-19 pandemic. This research uses a qualitative approach with a descriptive method. Sampling used a purposive sampling method with data collection using observation techniques and in-depth interviews. The study's findings indicate that (1) a high level of social capital as measured by networks, norms, and beliefs enables slum communities to survive the COVID-19 pandemic, and (2) the slum area communities' strategy for survival is to utilize yard land, home industries, social gathering, recitation, and mutual cooperation. There are several policy implications from this research: (1) Strengthen social capital, (2) Enhance community engagement, (3) Targeted support for vulnerable groups, (4) Ensure food security and (5) Strengthen social safety nets.